ON THE PROBLEM OF STUDYING PLACER MANIFESTATIONS WITH SMALL AND THIN GOLD IN THE NORTHERN BLACK SEA COAST OF UKRAINE - E.A. Sarvirov (Геологія і корисні копалини Світового океану, 2019)
The article is devoted to the urgent problem of studying objects with small and thin gold (STG) in loose deposits. In the literature, based on previously obtained data on the presence in the Cenozoic sedimentary sediments of southern Ukraine of samples with abnormally high alluvial gold contents, the Azov Black Sea alluvial province with STG was defined. The sources of gold supply in placers can be numerous deposits and ore occurrences of gold of the Ukrainian Shield (Sergeevskoye, Balka Zolotaya, Balka Shirokaya, Klintsovskoe, Mayskoye and others) located in the basins of the Dnieper and the Southern Bug. The total forecast resources of these deposits and occurrences are more 1 thousand tons. A significant part of the gold deposits has a fineness of less than 0.1 mm. During the denudation of ore bodies, STG in aggregates with iron hydroxides and clay minerals migrated to the river basins together with the pelite fraction and under favorable conditions could precipitate with the formation of gold deposits. It is noted that for the study of geological objects with STG, a particularly important role is played by the method of sampling and sample processing. The volume of an ordinary sample should be at least 0.04—0.06 m3. When processing the sample, a thorough separation of the clay fraction and its separate study is carried out. A fraction larger than 0.1 mm should be processed according to the gravity scheme using special enrichment devices, and a fraction smaller than 0.1 mm should be sent to the determination of gold by analytical methods. The general scheme of research on the distribution of sedimentary deposits with STG should include: structural and geomorphological analysis of the territory using materials from remote methods and the results of previous geological studies to identify promising areas and areas of probable sediment accumulation with STG; special testing of selected areas; local forecast of objects with industrial gold content.